NITROGEN MANAGEMENT STUDIES IN AUTUMN PLANTED MAIZE (ZEA MAYS L.) HYBRIDS - M. F. Saleem; M. S. Randhawa; S. Hussain; M. A. Wahid; S. A. Anjum (Journal of Animal and Plant Sciences, 2009)
A field experiment was conducted at Agronomic Research Area, University of Agriculture, Faisalabad, during autumn 2006 to evaluate the performance of two maize hybrids (R-2315, R-2331 ) under split dose of N application at different growth stages of crop plants (full N at sowing, half N at sowing + half N 25 DAS; 1/3 N at sowing + 1/3 N 25 DAS + 1/3 N at 55 DAS) and different methods of fertilizer application (broadcast and side placement/side dressing) to improve its efficiency. The experiment was laid out in randomized complete block design with split- split plot arrangement; keeping maize hybrids in main plot, time of N application in sub-plot and method of N application (M) in sub- sub plots. It was observed that maize hybrids were statistically similar for number of days taken to mature, number of grains per cob, 1000-grain weight, and grain yield while the timing and method of N application significantly affected the same parameters. The more number of days taken to mature (102.38), maximum number of grains per cob (519.00), 1000-grain weight (297.64 g) and grain yield (6.42 t ha-1) were recorded when 1/3 N was applied at sowing + 1/3 N at 25 DAS and 1/3 N 55 DAS as compared to other timings of N application at different growth stages of crop. Likewise, the higher number of days taken to mature (99.58), and higher number of grains per cob (514.17), 1000-grain weight (286.22 g) and grain yield (6.07 t ha-1) were recorded, when N was side dressed/side placed as compared to N application through broadcast in the same parameters. It was concluded that 1/3 N application at the time of sowing, 1/3 N application 25 DAS + 1/3 N application 55 DAS by side dressing/side placement was the best efficient methodology for N management, irrespective of the type of maize hybrid.
Keywords: Maize hybrids; time and method of N application; yield and its attributes